Case report: Reducing the duration of positive-pressure ventilation for large mediastinal masses - Zhang, Zaili; Jiang, Meiru; Sun, Xijia; Tan, Wenfei (Frontiers in Cardiovascular Medicine, 2022)
Large mediastinal masses (MMs) are rare and present some challenges in hemodynamic and airway management under general anesthesia. Multiple studies have reported cardiopulmonary collapse during general anesthesia. Maintenance of spontaneous ventilation, avoidance of muscle relaxants, and awake-intubation were usually recommended during general anesthesia for high-risk patients with large MMs. However, the recent notion challenged the classic teaching that maintaining spontaneous ventilation is superior to positive-pressure ventilation (PPV). In our case reports, we present two patients with large MMs during general anesthesia. In the first case, a 21-year-old male was administered a muscle relaxant during induction, followed by PPV, but his blood oxygen saturation decreased to 40% after 20 min. Finally, his oxygen saturation was restored by a sternotomy rather than by cardiopulmonary bypass (CPB) by femoral vascular intubation. In the second case, a 33-year-old male was also administered a muscle relaxant during induction followed by PPV, but for him, sternotomy was immediately performed, with stable blood oxygen saturation. Both patients recovered well and were discharged from hospital a week after surgery. Therefore, we present a recommendation that patients with large MMs could undergo PPV after the administration of a muscle relaxant during induction, but the cardiothoracic surgeon should immediately cleave the sternum.